2012
DOI: 10.3389/fcimb.2012.00045
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing Methods for the Emerging Campylobacter Species C. hyointestinalis, C. lanienae, C. sputorum, C. concisus, and C. curvus

Abstract: Multilocus sequence typing (MLST) systems have been reported previously for multiple food- and food animal-associated Campylobacter species (e.g., C. jejuni, C. coli, C. lari, and C. fetus) to both differentiate strains and identify clonal lineages. These MLST methods focused primarily on campylobacters of human clinical (e.g., C. jejuni) or veterinary (e.g., C. fetus) relevance. However, other, emerging, Campylobacter species have been isolated increasingly from environmental, food animal, or human clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 42 publications
(71 reference statements)
1
69
0
Order By: Relevance
“…MLST was performed as previously described under the conditions and with the primer sets of Miller et al (52,53). MLST amplifications were performed on a Tetrad thermocycler (Bio-Rad, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
“…MLST was performed as previously described under the conditions and with the primer sets of Miller et al (52,53). MLST amplifications were performed on a Tetrad thermocycler (Bio-Rad, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
“…For each housekeeping gene, the different sequences present within a bacterial species are assigned as distinct alleles, and for each isolate, the alleles at each of the loci define the allelic profile or sequence type (ST) (Dingle et al 2001). This technique has been used successfully to determine the sequence types of C. coli in pig liver (von Altrock et al 2013); C. jejuni in human, poultry, and bovine isolates (de Haan et al 2013); and C. hyointestinalis and other emerging campylobacters (Miller et al 2012). The MLST genotyping approach is less susceptible to factors causing genomic instability than earlier genomic methods using restriction site polymorphisms or single genetic markers (Wassenaar et al 2000).…”
Section: Multilocus Sequence Typing (Mlst)mentioning
confidence: 99%
“…Of the Campylobacter species for which DNA-based subtyping has been undertaken on appreciable numbers of strains, C. concisus appears to be the most polymorphic. Interestingly, despite the apparent lack of clonality as inferred in AFLP (Aabenhus et al, 2005;Kalischuk and Inglis, 2011;this study) or MLST analysis (Miller et al, 2012), the latter has not yet identified substantive recombination events between strains. Additional work is needed to resolve the population genetics of this intriguing species.…”
Section: Discussionmentioning
confidence: 77%
“…As in previous studies (Aabenhus et al, 2005;Kalischuk and Inglis, 2011), two major groups were revealed, that corresponded to GS1 (that includes CCUG 13144, the type strain of oral origin) and GS2 (that includes reference strains CCUG 19995 and RH 13826 from human gastroenteritis). No appreciable similarity between South African isolates was obtained with reference profiles of GS3 (RH 7656) and GS4 (RH 13570; which was indicated by MLST to be C. curvus : Miller et al (2012). On the other hand, two profiles were observed, that were highly distinctive and occupied well separated positions in the dendrogram, and potentially representing new C. concisus genomo-species (GS 5 and 6 respectively).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation